The Effect of Telehealth Utilization on the Efficiency of Nursing Services in Hospitals - Ika Subekti Wulandari (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
The use of digital technology in health services is rapidly increasing, particularly through telehealth. In referral hospitals, nursing service processes are often constrained by long patient waiting times, limited coordination among health workers, and inadequate continuous patient monitoring. These challenges highlight the need for service innovations that improve nursing efficiency without compromising care quality. This study aimed to analyze the effect of telehealth utilization on the efficiency of nursing services. A quantitative method with a cross-sectional design was applied. The study was conducted at Dr. Kariadi Hospital, Semarang, in 2025, involving a population of implementing nurses in inpatient units. A total of 120 nurses were selected using proportional random sampling. Data were collected through structured questionnaires assessing telehealth utilization and nursing service efficiency, along with service time observation sheets. Univariate analysis was used to describe frequency distributions, while bivariate analysis employed the Chi-Square test with a significance level of 0.05. The results showed that 68.3% of nurses had good telehealth utilization, and 71.7% demonstrated high efficiency in nursing services. There was a significant relationship between telehealth utilization and service efficiency (p = 0.001; OR = 3.45). Nurses with good telehealth utilization were 3.45 times more likely to provide efficient services. In conclusion, telehealth significantly improves nursing service efficiency, emphasizing the need for supportive policies, training, and system integration.